Experimental pain and fatigue induced by excessive chewing - Samaa Al Sayegh; Ioanna Vasilatou; Abhishek Kumar; Ceva Al Barwari; Lars Fredriksson; Anastasios Grigoriadis; Nikolaos Christidis (BMC, 2020)
Abstract Background The study was aiming to optimize excessive gum chewing as an experimental model to induce jaw muscle pain and fatigue similar to those in painful TMDs with durations that would allow immediate investigations of jaw-motor function. Further, if any sex differences would be detected in the expression of pain. Methods This randomized, double blinded study included 31 healthy participants of both sexes. A standardized chewing protocol of either 40- or 60-min of chewing was used with a wash-out period of 1 week. Subjective fatigue, pain characteristics and functional measures were assessed. For statistical analyses, Wilcoxon Signed Rank test, Mann-Whitney Rank Sum test and Friedman's ANOVA with Tukey post-hoc test were used. Results High subjective fatigue scores that lasted up to 20 min after the end of the trial were significantly induced both in the 40- and 60-min chewing trials (P <  0.001*). Significant but mild pain was induced only in the 60-min trial (P = 0.004*) and only in men (P = 0.04*). Also, the induced pain area was significantly bigger in the 60-min trial (P = 0.009*). However, this increase in pain and pain area did not last to the first 10-min follow-up. There were no significant differences neither between the 40- and 60-min chewing trials, except regarding the pain area (P = 0.008*), nor between the sexes. Conclusion Taken together, excessive chewing in its current form does not seem to be a proper pain experimental model. The model needs further adjustments in order to mimic TMD-pain especially in women and to prolong the pain duration.